Pertanggungjawaban Pidana dalam Kasus Perdagangan Orang Berkedok Program Magang Mahasiswa di Jerman: Kajian atas Modus Operandi dan Tantangan Hukum - Nurillah, Mutiara Asyifa; Ashghor, Aly; Melanie , Melanie Pita Lestari (Jurnal Keamanan Nasional, 2025)
The phenomenon of globalization has significantly increased human mobility, including the rise of student exchange programs and internships abroad. The alleged case of Trafficking in Persons in a student internship program in Germany raises concerns regarding exploitation in the form of a student internship program mode. This study aims to analyse whether this case meets the elements of TPPO based on Law No. 21 of 2007 concerning the Eradication of TPPO, as well as how the form of criminal liability for the perpetrators involved. This research uses a normative juridical method with a statutory and case approach. Data is obtained from literature study and legal analysis of related regulations. The results show that the elements of recruitment, fraud and exploitation in this case have the potential to fulfil the elements of TPPO as stipulated in Law No. 21 of 2007 concerning the Eradication of TPPO. The government is obliged to protect victims and tighten the regulation of overseas internship programs and conduct supervision related to internship programs carried out by students abroad.